The Livability Level of Settlements in Kelurahan Dalam Bugis: An Analysis of Waste Management Aspects and Fire Protection Systems - Inda Purnama; Agus Sugiarto; Sulistyarini (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2024)
The dynamic development of an area significantly impacts people's living patterns, particularly regarding settlement issues. One major issue in settlement development is the livability of the settlement. This research aims to identify the distribution of settlement livability levels based on waste management conditions and fire protection systems. The study was conducted in Kelurahan Dalam Bugis, East Pontianak District, Pontianak City. A mixed methods approach was used in this research. Spatial quantitative data were analyzed and presented using Geographic Information Systems, while qualitative data were presented through data reduction, documentation, observation, and field interviews. The results showed that 16.4% of settlements are categorized as light slums (livable), 0.7% as moderate slums (quite livable), and 82.9% as severe slums (not livable). Livable settlements cover an area of 32.54 hectares (1,706 housing units). Moderately livable settlements cover an area of 1.33 hectares (97 housing units). Uninhabitable settlements cover an area of 159.13 hectares (2,290 housing units). Mitigation of critical health and safety aspects, such as fire hazards, requires increasing public awareness of waste management and providing adequate waste processing and fire-fighting facilities to prevent unwanted events.